Pemanfaatan Big Data dan Artificial Intelligence (AI) dalam Optimalisasi Sistem Pendidikan Islam di Era Digital - Muhammad Faisal; Ahmad Khori; Mochamad Yaqub Sulaeman (STKIP Subang, 2026)
The rapid advancement of digital technologies, particularly Big Data and Artificial Intelligence (AI), presents both significant opportunities and considerable challenges for Islamic education institutions in Indonesia. This study aims to analyze the potential and obstacles of integrating these technologies into Islamic educational systems, as well as to formulate a conceptual framework for their integration that remains consistent with Islamic values. The methodology employed is a Systematic Literature Review (SLR), drawing on Sinta indexed journals and other relevant scientific publications from 2018 to 2025. Findings indicate that Big Data has the potential to enhance data-driven decision-making in Islamic educational institutions, while AI enables more adaptive and personalized learning experiences. Nevertheless, implementation remains constrained by low digital literacy among educators, limited technological infrastructure, and concerns over the erosion of core Islamic educational values. The study concludes that the integration of technology in Islamic education must be carried out in a gradual, inclusive, and value-based manner. The TPACK (Technological Pedagogical Content Knowledge) framework is proposed as the most operationally relevant guide for this integration process.